Mitral regurgitation: etiology, pathogenesis, diagnosis, and outcomes - D. Yu. Andriyashkina; N. A. Demidova; K. R. Gevondyan; A. A. Klimenko (Рациональная фармакотерапия в кардиологии)
Managing a patient with mitral regurgitation (MR) is a difficult task. Degenerative and ischemic changes are the main causes of MR in developed countries, while rheumatic valve changes predominates in developing countries. MR progression occurs gradually and often imperceptibly, which is associated with the compensatory mechanisms of the heart, and leads to left ventricular remodeling and worsens prognosis. The clinical improvement in the patient condition with acute MR after the appearance of heart failure signs is obviously due to a gradual increase in the left atrium and atrial pressure decrease. The initial assessment of MR suggests the presence of heart failure clinical symptoms, which develop as MR volume increases and left ventricular systolic dysfunction worsens. However, these data are insufficient to determine the indications for surgery. Echocardiographic methods should be used to quantify the severity of the defect. The only proven treatment to improve symptoms and prevent heart failure is surgery. The annual mortality rates for surgical treatment in patients aged 50 years and older are about 3% for moderate and 6% for severe MR. Valve-preserving operations are superior in results to prosthetics and reduce mortality in patients with severe organic MR by 70%. The morphology of the valve apparatus lesion is crucial for the successful operation. The consequences of severe rheumatic valve damage limit the possibility of valve repair. If it is impossible to perform valve repair, it is preferable to perform prosthetics of the valve while maintaining the subvalvular apparatus. The best short-term and long-term results of surgical treatment were obtained in asymptomatic patients operated in specialized centers. This highlights the importance of MR early detection and assessment.